Psychological Distress During the COVID-19 Pandemic in Patients With Mental or Physical Diseases - Oppenauer, Claudia; Burghardt, Juliane; Kaiser, Elmar; Riffer, Friedrich; Sprung, Manuel (Frontiers in Psychology, 2021)
The coronavirus disease 2019 (COVID-2019) and the consequences of the pandemic on individuals’ social, economic, and public lives are assumed to have major implications for the mental health of the general population but also for patients already diagnosed with psychological disorders. The aim of the present study was to investigate the psychological distress during the COVID-19 pandemic in patients with psychological disorders or physical health conditions in inpatient mental and physical treatment programs. 2710 patients completed COVID-19 related questions concerning their psychological distress and financial burden during the pandemic. Patients with psychological disorders reported the highest level of psychological distress and financial burden compared to patients with physical health conditions. Furthermore, most patients with psychological disorders attributed their individual psychological distress to the COVID-19 pandemic. In comparison to patients with physical health conditions, patients with psychological disorders are more strongly impacted by the COVID-19 pandemic and have an additional need for psychological/psychotherapeutic treatment due to the COVID-19 crisis. The findings stress the importance of continuous psychosocial support and availability of psychosocial support services for patients with psychological disorders during the pandemic.